Cyclodextrin-Assisted Extraction Method as a Green Alternative to Increase the Isoflavone Yield from Trifolium pratensis L. Extract - Jurga Andreja Kazlauskaite; Liudas Ivanauskas; Jurga Bernatoniene (Pharmaceutics, 2021)
Trifolium pratense L. is receiving increasing attention due to the isoflavones it contains, which have been studied for their benefits to human health. A common problem with isoflavone aglycones is a rather low water solubility and limited pharmaceutical applications. The use of excipients, such as cyclodextrins in the production of isoflavone rich extracts, could become one of the new strategies for the extraction of target compounds. The aim of this study was to evaluate an eco-friendly method using the effects of α-, β- and γ-cyclodextrins for isoflavone solubilization in plant extracts in comparison to a standard extract without excipients. Extractions of red clover were prepared using ultrasound-assisted combined with thermal hydrolysis and heat reflux. It was determined that cyclodextrins significantly increased the isoflavones aglycone yields. By increasing cyclodextrins in the extraction media from 1 to 5%, the daidzin concentration increased on average by 1.06 (α-cyclodextrins), 1.4 (β-cyclodextrins) and 1.25 (γ-cyclodextrins) times. Genistein concentration increased using α- and γ-cyclodextrins (1.28 and 1.12 times, α- and γ-cyclodextrins, respectively), but decreased using β-cyclodextrins. The results showed that the cyclodextrin-assisted extraction enhanced the yields of isoflavones from red clover, which suggests using cyclodextrins as a green alternative and a cost-effective method to increase its pharmaceutical application.